2014
DOI: 10.1097/mib.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Hospitalizations in Inflammatory Bowel Disease Among Children in the United States, 1988–2011

Abstract: Background Our objective was to characterize national trends in inflammatory bowel disease (IBD)-related hospitalizations for children. We hypothesized that over time, improvements in care would be associated with a decrease in hospitalization rates, similar to what has been observed in Canadian children with IBD. Methods Retrospective, serial, cross-sectional analysis of annual, nationally representative samples of children with IBD. Results Overall, discharges for all children irrespective of diagnosis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…1 Recent studies indicate that hospitalizations are increasing for children with inflammatory bowel diseases (IBD) in the US. 2,3 In addition, a Canadian study demonstrated that pediatric patients with IBD are at greater risk for hospital readmission compared with older patients. 4 These trends are cause for concern to both patients and payers, as hospitalization of pediatric patients with IBD has been associated with a significant cost burden 57 and hospitalization has been associated with decreased health-related quality of life in other populations of children with chronic diseases.…”
mentioning
confidence: 99%
“…1 Recent studies indicate that hospitalizations are increasing for children with inflammatory bowel diseases (IBD) in the US. 2,3 In addition, a Canadian study demonstrated that pediatric patients with IBD are at greater risk for hospital readmission compared with older patients. 4 These trends are cause for concern to both patients and payers, as hospitalization of pediatric patients with IBD has been associated with a significant cost burden 57 and hospitalization has been associated with decreased health-related quality of life in other populations of children with chronic diseases.…”
mentioning
confidence: 99%
“…Patients with IBD require more frequent hospital admissions than non-IBD patients, with an increased average length of stay not only in the United States but also globally. 1,2 Moreover, hospital care for IBD patients has been shown to be twice as expensive as that for non-IBD controls. 3 Repeat hospitalization in subgroups of IBD patients seems to be a large part of this issue 4,5 ; however, there is only limited literature examining the characteristics of IBD patients who are associated with frequent hospital use.…”
mentioning
confidence: 99%
“…The combination of diagnosis codes used in defining the sample has been described previously. 9,1719 We excluded discharges with codes of other forms of colitis (eosinophilic, allergic, microscopic, and ischemic) as well as discharges with codes for both CD & UC. Discharges with CDI were captured using the ICD-9-CM code of 008.45; this is the only code devoted to CDI, has been previously validated as an accurate determinant of active CDI.…”
Section: Methodsmentioning
confidence: 99%
“…11 To evaluate trends over time, the P for trend test was conducted using variance-weighted least-squares regression, demonstrated previously. 9,2426 Trends were analyzed over 1997–2011 as yearly point estimates with 95% confidence intervals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation